2022
DOI: 10.1002/pld3.393
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum root epigenetic landscape during limiting phosphorus conditions

Abstract: Efficient acquisition and use of available phosphorus from the soil is crucial for plant growth, development, and yield. With an ever‐increasing acreage of croplands with suboptimal available soil phosphorus, genetic improvement of sorghum germplasm for enhanced phosphorus acquisition from soil is crucial to increasing agricultural output and reducing inputs, while confronted with a growing world population and uncertain climate. Sorghum bicolor is a globally important commodity for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…The seeds were then germinated in moistened filter paper. Four days after germination, seedlings with similar growth vigor were transferred to 100 L polypropylene tubs and grown hydroponically using a specially designed and constructed plant growth pouch system, which holds the seedling and root system on the surface of filter paper, as described by Gladman et al ( 2022 ). The full strength nutrient solution contains: 1 mM Ca(NO 3 ) 2 ·4H 2 O, 1 mM NH 4 NO 3 , 1 mM KCl, 0.85 mM MgSO 4 ·7H 2 O, 0.25 mM NH 4 H 2 PO 4 , 77 μM Fe-EDTA, 25 μM H 3 BO 3 , 0.8 μM Na 2 MoO 4 ·2H 2 O, 0.6 μM CuSO 4 ·5H 2 O, 9 μM MnCl 2 ·4H 2 O, 2 μM ZnSO 4 ·7H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…The seeds were then germinated in moistened filter paper. Four days after germination, seedlings with similar growth vigor were transferred to 100 L polypropylene tubs and grown hydroponically using a specially designed and constructed plant growth pouch system, which holds the seedling and root system on the surface of filter paper, as described by Gladman et al ( 2022 ). The full strength nutrient solution contains: 1 mM Ca(NO 3 ) 2 ·4H 2 O, 1 mM NH 4 NO 3 , 1 mM KCl, 0.85 mM MgSO 4 ·7H 2 O, 0.25 mM NH 4 H 2 PO 4 , 77 μM Fe-EDTA, 25 μM H 3 BO 3 , 0.8 μM Na 2 MoO 4 ·2H 2 O, 0.6 μM CuSO 4 ·5H 2 O, 9 μM MnCl 2 ·4H 2 O, 2 μM ZnSO 4 ·7H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…Buckwheat, classified as a legume, can capture atmospheric nitrogen via the action of nitrogen-fixing bacteria, resulting in the enhancement of soil fertility with this vital nutrient [37]. The wide fibrous root structure of S. bicolor, capable of growing to great depths, improves soil aggregation and water penetration, facilitating nutrient absorption and enhancing soil fertility [50,51]. P. millet's shallow root system is advantageous for nutrient absorption and soil structure enhancement, particularly in less fertile soils [52,53].…”
Section: Implication Of P Millet S Bicolor and Common Buckwheat Rotat...mentioning
confidence: 99%
“…Soybean plants grown under low-P condition showed a reduction in the growth of the primary root with the induction of lateral roots and root hairs (Zhu et al, 2020). Several works have revealed the response of plants to low P by altering root morphology and their root properties (Hiradate et al, 2007;Niu et al, 2013;Hufnagel et al, 2014;Muller et al, 2015;Huang et al, 2019;Wu et al, 2019;Barros et al, 2020;Tang et al, 2020;Gladman et al, 2022;Chen et al, 2022;Mo et al, 2022).…”
Section: Alteration Of Root Architecture In Sorghum and Other Plantsmentioning
confidence: 99%
“…In contrast, root length of sensitive inbred lines and the sensitive parent B-69 was greatly inhibited by low P conditions, as well as root volume and the number of proteoid roots (Table 3). Gladman et al (2022) showed that during limiting P condition, sorghum RSA (root architecture structure) was renovated to increase root length and surface area, likely enhancing its ability to acquire P. Hubnagel et al ( 2014) mentioned that the rice protein kinase, PHOSPHORUS-STARVATION TOLERANCE1 (OsPSTOL1) has shown to enhance P acquisition and grain yield in rice under P deficiency. Their study indicated that multiple SbPSTOL1 genes have a more general role in the root system, not only enhancing root morphology traits but also changing root architecture, which leads to grain yield gain under low-P availability in the soil.…”
Section: Alteration Of Root Architecture In Sorghum and Other Plantsmentioning
confidence: 99%
See 1 more Smart Citation